Individual Projects as a Deep Learning Pedagogy Strategy for Package C Students - Nelly Tarwiyati; Luthfi Wibawa; Yudan Hermawan (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2025)
This study aims to analyze the implementation of the individual project as a strategy for deep learning pedagogy within the Paket C equivalency program at ABhome Education. Using a qualitative approach with a case study design, the research involved 11 informants, including institutional leaders, facilitators, mentors, and students. Data were collected through observations, in-depth interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that the individual project effectively creates a student-centered learning environment through four key components. First, interest-based project planning enables students to develop agency, intrinsic motivation, and meaningful learning goals. Second, the implementation stage provides authentic learning experiences that enhance critical thinking, problem-solving abilities, and learner autonomy. Third, reflection through the 4E formula (Enjoy, Easy, Excellent, Earn) strengthens metacognitive awareness and self-evaluation skills. Fourth, mentors act as learning partners who offer reflective scaffolding without limiting students’ independence. Overall, the integration of PDCA and 4E reflection supports joyful, meaningful, and mindful learning while reinforcing 21st-century competencies. These findings highlight that the individual project approach is an effective strategy for operationalizing deep learning pedagogy in non-formal education settings.